К проблеме языковой компетенции детей 7–10 лет из семей мигрантов, не владеющих или слабо владеющих русским языком - Kuzmina K. V. (Academic community of students, 2016)
The article deals with the theoretical analysis of the problems of language competence of younger pupils from migrant families, also presents a theoretical review of the literature reveals the contents of the "language competence" of the concept and its structure.
Keywords: дети; коммуникативная компетенция; адаптация; языковая компетенция; adaptation; Communicative Competence; language competence; children from migrant families; семьи мигрантов